2001
DOI: 10.2105/ajph.91.11.1882
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Behaviors and Perceptions Among Adults in 25 States: 1997 Behavioral Risk Factor Surveillance System

Abstract: Most US adults do not engage in HIV-related risk behavior; those that do are more likely to report protective behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
8
25
1
2
Order By: Relevance
“…A previous study, however, estimated that these individuals had negligible effect on results. 13 Finally, as with all observational studies that rely on self-report, subjects may have under-or over-reported their HIV risk behaviors and HIV testing practices. Given the sensitive nature of HIV risk behavior questions, subjects may have provided socially desirable responses leading to under-reporting of HIV risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study, however, estimated that these individuals had negligible effect on results. 13 Finally, as with all observational studies that rely on self-report, subjects may have under-or over-reported their HIV risk behaviors and HIV testing practices. Given the sensitive nature of HIV risk behavior questions, subjects may have provided socially desirable responses leading to under-reporting of HIV risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are best monitored through representative sampling of the general U.S. population to measure risk behaviors and HIV-testing behaviors. 17,18 Behavioral surveillance also must include the collection of data from infected populations and populations at increased risk for infection. Populations at increased risk for acquiring HIV infection in the United States include MSM, injecting drug users (IDUs), and highrisk heterosexuals who engage in risky behaviors or have HIV-infected partners (HET).…”
Section: Conceptual Framework Of the Key Behaviors And Populations Fomentioning
confidence: 99%
“…2 Risk behavior data are used to assess the prevalence of risk behaviors at a point in time, monitor trends in these behaviors over time, assess the co-occurrence of risk behaviors, and identify demographic and social correlates of risk. 5,6 Monitoring testing behaviors in the general population is appropriate because HIV testing programs are not always targeted to specific groups. Data from general population surveys can be used for assessing progress toward health objectives related to HIV testing, such as CDC's HIV Prevention Strategic Plan 1 or Healthy People 2010; 7 evaluating national policies or guidelines on HIV testing; 8,9 and evaluating the use of new testing technologies, such as oral fluid tests and rapid tests.…”
mentioning
confidence: 99%